A Conceptual Framework for Mentorship Support to Early-Career Black Women Academics in South Africa - Maréve Biljohn; Tatenda Shaleen Marange; Aliza le Roux; Kathleen Schroeder (African Journal of Inter-Multidisciplinary Studies)
Globally, career development is a challenge for women academics at higher education institutions. In South African higher education institutions, Black women academics still lag in terms of career progression and their representation in leadership positions compared to their male counterparts.  While structural and systemic challenges contribute to this, a lack of formal mentorship support for Black women academics is among the underlying reasons. Against this background, using various mentorship models applied in higher education institutions as the theoretical lens, this article explores a conceptual framework for mentorship support to early-career Black women academics, which will often happen in a cross-cultural context due to historical imbalances. Through a qualitative research approach, a narrative literature review is provided based on content analysis of literature, both peer-reviewed and non-reviewed. Through a conceptual framework, this study provides insight regarding the type of mentorship support that is required to advance the career development trajectory of early-career Black women academics in South Africa, considering the paucity of women’s mentorship programs at most of our higher education institutions. Recommendations propose how mentorships can be integrated into the formal career development trajectory of these academics.